Assessment of ?Imtiaz?s Sign? for Early Detection of Hypovitaminosis A - , Safdar Ali Abbasi, Shabir Ahmad Bhutto, Syed Imtiaz Ali Shah, Shujaat Ali Shah, Partab Rai, Shahid Jamal Siddiqui (Pakistan Journal of Ophthalmology, 2015)
Purpose: To identify and document the earliest diagnostic sign of vitamin A deficiency (Imtiaz's sign). Material and Methods: This prospective case series study was conducted from September 1999 to September 2014 at ophthalmology department Chandka medical college and Syed eye clinic, Larkana, Pakistan. Patients identified clinically as cases of hypovitaminosis A on the basis of presence of “Imtiaz’s sign” were included in the study. Patients with Retinitis pigmentosa, glaucoma, chronic liver disease and malabsorption syndrome were excluded from the study. Imtiaz's sign of vitamin A deficiency and nyctalopia were noted and relevant laboratory investigations available were also done on selected patients. Patients were given therapeutic doses of vitamin A and improvement was observed to see resolution of Imtiaz’s sign of vitamin A deficiency and remission of nyctalopia. Results: 650 patients, 152 (23.38%) males and 498 (76.62%) females were identified as cases of hypovitaminosis A on the basis of presence of Imtiaz’s sign. Age of the patients ranged from 5 to 43 years and the mean age (± standard deviation) was 18.15 ± 10.20 years. All patients replied positively for nyctalopia; however other signs, except Imtiaz’s sign, were not observed due to the early stage of vitamin A deficiency. Relevant laboratory investigations were performed on selected cases which showed that 45.68% of them had iron deficiency, 40.74% of them had hypoalbuminemia and 13.58% had disturbed LFTs. This shows that most of the patients suffering from vitamin A deficiency were victims of malnourishment. Conclusion: Imtiaz’s sign is an early and effective clinical diagnostic sign to identify vitamin A deficiency at an early phase. It requires no costly tools for application, is safe and can be easily recognized and treated by vitamin A supplements. Such a diagnostic ocular sign is desirable to avoid morbidity and mortality related to vitamin A deficiency. Keywords: Blindness, Malnutrition, Vitamin A deficiency, Xerophthalmia.